Michel Houellebecq Humanity and its Aftermath - Morrey, Douglas (Contemporary French and Francophone Cultures, 2013)
Michel Houellebecq is perhaps the single most successful and controversial of all contemporary novelists writing in French. Houellebecq has become a global publishing phenomenon: his books have been translated worldwide, three film adaptations of his work have been produced, and the author has been the subject of million-euro publishing deals and of successive media scandals in France. His novels narrate a metaphysical mutation or paradigm shift through which humanity as we know it ceases to be the over-riding value or focus of our world when it comes into conflict with a competitor in the form of a post-human or neo-human species. It is the aim of this book to appraise the global significance of Houellebecq's novelistic visions while at the same time situating them within the context of French literature, culture and society.